Effect of two counseling interventions on self-reported alcohol consumption, alcohol biomarker phosphatidylethanol (PEth), and viral suppression among persons living with HIV (PWH) with unhealthy alcohol use in Uganda: A randomized controlled trial. (1st March 2023) - Hahn, Judith A.; Fatch, Robin; Emenyonu, Nneka I.; Sanyu, Naomi; Katusiime, Anita; Levine, Barry; John Boscardin, W.; Chander, Geetanjali; Hutton, Heidi; Camlin, Carol S.; Woolf-King, Sarah E.; Muyindike, Winnie R.
Abstract: Purpose: To test the efficacy of two interventions to reduce alcohol use and increase viral suppression compared to a control in persons with HIV (PWH). Methods: In a three-arm (1:1:1) randomized controlled trial (N = 269), we compared in-person counselling (45–70 minutes, two sessions over three months) with interim monthly booster phone calls (live call arm) or twice-weekly automated booster sessions (technology arm) to a brief advice control arm. We enrolled PWH self-reporting unhealthy alcohol use (Alcohol Use Disorders Identification Test – Consumption, prior three months, women ≥3, men ≥4). Primary outcomes were number of self-reported drinking days (NDD) in the prior 21 and biomarker phosphatidylethanol (PEth) at six and nine months and viral suppression (<40 copies/mL) at nine months; we adjusted for sex and baseline outcomes. Results: At baseline, mean 21-day NDDs were 9.4 (95 % CI: 9.1–9.8), mean PEth was 407.8 ng/mL (95 % CI: 340.7–474.8), and 89.2 % were virally suppressed. At follow-up, there were significant reductions in mean NDDs for the live call versus control arm (3.5, 95 % CI:2.1–4.9, p < 0.001) and for the technology versus control arm (3.6, 95 % CI: 2.2–5.1, p < 0.001). The mean PEth differences compared to the control arm were not significant, i.e. 36.4 ng/mL (95 % CI: −117.5 to 190.3, p = 0.643) for the live call and −30.9 ng/mL (95 % CI: −194.8 to 132.9, p = 0.711) for the technology arm. Nine-month viral suppression compared to the control was similar in the live call and in the technology arm. Conclusion: Intervention effects were found on self-reported NDD but not PEth or viral suppression, suggesting no treatment effect. (NCT #03928418) Highlights: Alcohol counselling affected self-reported alcohol use but not phosphatidylethanol (PEth). The discrepancy between self-report and PEth was likely due to social desirability bias. Future trials of brief alcohol interventions should incorporate alcohol biomarkers.